2013
DOI: 10.4103/1119-3077.113465
|View full text |Cite
|
Sign up to set email alerts
|

Teachers′ knowledge and attitudes towards seizure disorder: A comparative study of urban and rural school teachers in Akwa Ibom State, Nigeria

Abstract: School teachers in both urban and rural schools exhibited poor knowledge and negative attitudes towards children with seizure disorder. Residing in the urban setting did not have a positive impact on teachers' perception of seizure disorder. Massive health education on seizure disorder is therefore advocated for teachers in both urban and rural schools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 16 publications
4
16
1
Order By: Relevance
“…This finding is similar to other reports from sub – Saharan Africa [18, 20, 21]. The community study participants had limited knowledge about causes and characterisation of epilepsy which is also in agreement with other reports from sub – Saharan Africa [22, 23].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is similar to other reports from sub – Saharan Africa [18, 20, 21]. The community study participants had limited knowledge about causes and characterisation of epilepsy which is also in agreement with other reports from sub – Saharan Africa [22, 23].…”
Section: Discussionsupporting
confidence: 92%
“…In contrast to earlier studies, the study populations are different. Earlier studies have mostly been conducted within specific community groups such as teachers, traditional healers, university students, literate urban population and secondary school students [17, 21, 24]. This might explain the poorer knowledge of epilepsy in our populations.…”
Section: Discussionmentioning
confidence: 99%
“…However the study results disagree with [23], who studied" teachers' knowledge, attitudes and practices towards seizure disorder: a comparative study of urban and rural teachers in AkwaIbom State, Nigeria", and found significant difference between total score practices and attitudes among studied samples regarding epilepsy post program.…”
Section: Discussioncontrasting
confidence: 54%
“…6 Children experiencing cognitive difficulties due to the side effects of AED's or due to the severity of the condition itself may be regarded as lazy by both teachers and parents. 7,8 Added to these factors are the perception of epilepsy as a manifestation of supernatural forces, taboos, contagious and spread by body fluids [9][10][11] which lead to high levels of stigma in SSA.…”
Section: Introductionmentioning
confidence: 99%